Contrasting Patterns in Diversity and Community Assembly of Phragmites australis Root-Associated Bacterial Communities from Different Seasons - He, Rujia (Appl Environ Microbiol, 2020)
The common reed (Phragmites australis), a cosmopolitan aquatic macrophyte, plays an important role in the structure and function of aquatic ecosystems. We compared bacterial community compositions (BCCs) and their assembly processes in the root-associated compartments (i.e., rhizosphere and endosphere) of reed and bulk sediment between summer and winter. The BCCs were analyzed using high-throughput sequencing of the bacterial 16S rRNA gene; meanwhile, null-model analysis was employed to characterize their assembly mechanisms. The sources of the endosphere BCCs were quantitatively examined using SourceTracker from bulk sediment, rhizosphere, and seed. We observed the highest α-diversity and the lowest β-diversity of BCCs in the rhizosphere in both seasons. We also found a significant increase in α- and β-diversity in summer compared to that in winter among the three compartments. It was demonstrated that rhizosphere sediments were the main source (∼70%) of root endosphere bacteria during both seasons. Null-model tests indicated that stochastic processes primarily affected endosphere BCCs, whereas both deterministic and stochastic processes dictated bacterial assemblages of the rhizosphere, with the relative importance of stochastic versus deterministic processes depending on the season. This study suggests that multiple mechanisms of bacterial selection and community assembly exist both inside and outside P. australis roots in different seasons. IMPORTANCE Understanding the composition and assembly mechanisms of root-associated microbial communities of plants is crucial for understanding the interactions between plants and soil. Most previous studies of the plant root-associated microbiome focused on model and economic plants, with fewer temporal or seasonal investigations. The assembly mechanisms of root-associated bacterial communities in different seasons remain poorly known, especially for the aquatic macrophytes. In this study, we compared the diversity, composition, and relative importance of two different assembly processes (stochastic and deterministic processes) of bacterial communities associated with bulk sediment and the rhizosphere and endosphere of Phragmites australis in summer and winter. While we found apparent differences in composition, diversity, and assembly processes of bacterial communities among different compartments, season played important roles in determining BCCs and their diversity patterns and assemblages. We also found that endosphere bacteria mainly originated from the rhizosphere. The results add new knowledge regarding the plant-microbe interactions in aquatic ecosystems.